(untitled) (Canadian Dermatology Today, 2021)
Chronic urticaria (CU) occurs when pruritic wheals and/or angioedema manifests on most days of the week and persists for at least 6 weeks. Recent evidence suggests that the point prevalence of pediatric CU is similar to adults, affecting 0.5%-1.5% of children, with no sex predilection. While 20% of CU cases have an underlying physical/inducible trigger (chronic inducible urticaria, CIndU), in most cases the hives occur spontaneously (chronic spontaneous urticaria, CSU).